Efektivitas Penggunaan Bahasa Isyarat dalam Memahami Pembelajaran Bahasa Indonesia Siswa Kelas IV/ B Tuna Rungu di SLB Bhakti Luhur Baumata Kupang - Holbala, Grace Lady M.; Wangge, Vinsensius; Selan, Ot Bil Wilson; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
Language is a medium of communication. In this world, there are many languages, one of which is Sign Language. Sign Language is a communication system that utilizes body and visual movements, not just hand signals. In addition to the use of sign language, learning methods are also developing to improve the understanding of deaf students, which is gesture-based, which includes body movements and expressions. This study aims to determine the Effectiveness of Using Sign Language in Understanding Indonesian Language Learning for Grade IV/B Deaf Students at SLB Bhakti Luhur Baumata Kupang. The method used is Classroom Action Research with a quantitative descriptive approach based on the Kemiis and McTaggart model which includes 4 stages: Planning, implementation, observation and reflection. The research subject was 1 person, namely 1 woman. Data were collected through observation sheets of students. The results of the study in the first cycle showed an increase in understanding Indonesian language learning using Sign Language. Thus, it can be concluded that Indonesian and Sign Language with contextual activities with environmental themes make it easier for students to understand the material, improve fine motor coordination, and foster an attitude of caring for the environment